Peptide Folding and Binding Probed by Systematic Non-canonical Mutagenesis - Rogers, Joseph M. (Frontiers in Molecular Biosciences, 2020)
Many proteins and peptides fold upon binding another protein. Mutagenesis has proved an essential tool in the study of these multi-step molecular recognition processes. By comparing the biophysical behaviour of carefully selected mutants, the concert of interactions and conformational changes that occur during folding and binding can been separated and assessed. Recently, this mutagenesis approach has been radically expanded by deep mutational scanning methods, which allow for many thousands of mutations to be examined in parallel. Furthermore, these high-throughput mutagenesis methods have been expanded to include mutations to non-canonical amino acids, returning peptide structure-activity relationships with unprecedented depth and detail. These developments are timely, as the insights they provide can guide the optimization of de novo cyclic peptides, a promising new modality for chemical probes and therapeutic agents.